Design of Biomass Stove Using the Quality Function Deployment (QFD) Method - Yohanes Yohanes; Helmi Afianda Azhar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
The design of the furnace used by the community is still very simple so that the combustion efficiency is still low. This study aims to design and test the performance of a wood stove based on the wishes and needs of the community. This study uses a descriptive design. The sample of this research is 50 respondents. The measuring instruments of this research are questionnaires and field observations. The method in this study uses the Quality Function Deployment (QFD) method in analyzing the wood stove production design and the House of Quality matrix is ​​used in making the design to determine the characteristics of the community. The wood stove design used is two wood stoves. In the manufacture of this biomass furnace using mild steel material. The results showed that two wood stoves and one wood stove produced a faster boiling time than one wood stove, namely 4 minutes 52 seconds for two wood stoves, while for one wood stove it took 5 minutes 31 seconds. The difference in time obtained from these two tools is 39 seconds. The results of this study indicate that two wood stoves are more effective than one stove. This study recommends that people can use wood fuel when cooking, so it is easier than one biomass stove.